17α-Ethynylestradiol alters the peritoneal immune response of gilthead seabream. (November 2017) - Gómez González, N.E.; Cabas, I.; Rodenas, M.C.; Arizcun, M.; Mulero, V.; García Ayala, A.
Abstract: 17α-Ethynylestradiol (EE2 ), a synthetic estrogen used in most oral contraceptives pills and hormone replacement therapies, is found in many water bodies, where it can modulate the fish immune response. EE2 acts as an endocrine disruptor in gilthead seabream, Sparus aurata L., a marine teleost fish of great economic value in Mediterranean aquaculture, as it induces hepatic vitellogenin gene ( vtg ) expression. Moreover, EE2 also alters the capacity of gilthead seabream to appropriately respond to infection although it does not behave as an immunosuppressor. Nevertheless, these previous studies have mainly focused on the head kidney leukocytes and no information exists on peritoneal leukocytes, including mast cells. In the present work, juvenile gilthead seabream fish were fed a pellet diet supplemented with EE2 for 76 days and intraperitoneally injected with hemocyanin plus imject alum adjuvant at the end of EE2 treatment and 92 days later, and the peritoneal immune response was analyzed. EE2 supplementation induced vtg e xpression but returned to basal levels by 3 months post-treatment. Interestingly, gilthead seabream peritoneal leukocytes express the genes encoding for the nuclear estrogen receptor α and the G protein-coupled estrogen receptor 1 and the dietary intake of EE2 induced these expression. Moreover, EE2 induced an inflammatory response in the peritoneal cavity in unvaccinated fish, which was largely maintained for several months after the cessation of the treatment. However, the impact of EE2 in vaccinated fish was rather minor and transient. Taken together, the study provides fresh information about endocrine immune disruption, focusing on peritoneal leukocytes. Highlights: Gilthead seabream peritoneal leukocytes express the genes encoding for erα and gper1 . EE2 modulates the expression of both erα and gper1 . EE2 induces an inflammatory response in gilthead seabream peritoneal exudate. EE2 increases the expression of csf1r, ighm, ight and il1b and ROS production. EE2 effects were largely maintained for several months after cessation of treatment.